Anticoagulants for atrial fibrillation: from warfarin and DOACs to the promise of factor XI inhibitors - Kumar, Vineet; Ilkhanoff, Leonard (Frontiers in Cardiovascular Medicine, 2024)
Atrial fibrillation (AF) is the most prevalent arrhythmia in the world impacting over 46 million individuals. AF is a frequent and major cause of stroke, affecting approximately 800,000 individuals in the United States annually, of which three-quarters are new strokes, leading to significant healthcare resource expenditure (1). Most strokes asso-ciated with AF are cardioembolic, precipitated by the formation of thrombus within the left atrial appendage which then embolizes and impedes blood flow supplying brain tissue leading to neurologic impairment. Cardioembolic strokes related to AF have a significantly high rate of recurrence without treatment (2). Anticoagulation is the mainstay of stroke prevention in patients with AF. Current Amer-ican Heart Association and Heart Rhythm Society (AHA/HRS) guidelines recommend oral anticoagulation to reduce the risk of stroke in patients with AF with an elevated CHA2DS2VASC (congestive heart failure; hypertension, age ≥ 75 years; diabetes melli-tus; vascular disease (prior MI, PAD, or aortic plaque), age 65-74 years; female sex) score of ≥3 for women and ≥2 for men (2). Despite a decades long history supporting anticoagulant use to reduce stroke risk, no anticoagulant to date has proven to provide absolute protection against stroke without increasing the risk of bleeding.